2011
DOI: 10.1017/s0790966700011939
|View full text |Cite
|
Sign up to set email alerts
|

Exhaustion, depression and hopelessness in cardiac patients: a unidimensional hierarchy of symptoms revealed by Mokken scaling

Abstract: Objectives: Depression and vital exhaustion are associated with poor cardiovascular prognosis, but there is substantial overlap between these constructs. Factor analytic studies have been inconclusive, and may not be the optimal analytic strategy to assess dimensionality. We assessed whether exhaustion and depression formed a single, hierarchical dimension using a form of nonparametric item response theory.Methods: Patients with acute coronary syndrome (n = 430) completed questionnaires assessing depression an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Item 14 could be criticized as having lost its cultural relevance and ability to assess anhedonia as it is intended to and has been shown to have poor discriminative abilities (28,48). The validity of this item has been questioned in acute medical wards (11), suggesting that these activities may never be enjoyed in the hospital environment in which the HADS is completed.…”
Section: Discussionmentioning
confidence: 99%
“…Item 14 could be criticized as having lost its cultural relevance and ability to assess anhedonia as it is intended to and has been shown to have poor discriminative abilities (28,48). The validity of this item has been questioned in acute medical wards (11), suggesting that these activities may never be enjoyed in the hospital environment in which the HADS is completed.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, they found that the highest difficulty rating was for "Felt that life wasn"t worth living", whereas the lowest difficulty was found for "Been (un)able to face up to your problems", possibly indicating that the extreme feeling of hopelessness is commonly preceded by an inability to cope with problems. Similarly, in a sample of cardiac patients, Doyle et al (2011) showed that depressive symptom items showed a hierarchical form reflecting prevalence: fatigue (41%-75%), depression (21%-38%) and hopelessness (10-11%). Finally, it is not just negative emotions that may be hierarchical, as recent findings suggest that happiness may also have such a structure (Stewart et al, 2010).…”
Section: Introductionmentioning
confidence: 88%
“…Loevinger’s H coefficient is a measure of the number of Guttman errors in the data compared with the number that would be expected by chance. A Guttman error is where a person produces a paradoxical response such as endorsing a high-difficulty item while failing to endorse a low-difficulty one [8]. Guttman errors indicate that the two items do not measure the same trait.…”
Section: Methodsmentioning
confidence: 99%
“…Guttman errors indicate that the two items do not measure the same trait. Loevinger’s H value equals [1 – (actual Guttman errors/predicted Guttman errors)] [8]. The scalability coefficient for each item ( H i ), item pair ( H ij ), whole scale ( H ) and transposed Mokken scale ( H T ) may range from 0 to 1 [32, 37].…”
Section: Methodsmentioning
confidence: 99%